2017
DOI: 10.9790/1959-0603024854
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Testicular Self-Examination among Male Undergraduate Students in a Tertiary Institution in Calabar, Cross River State Nigeria

Abstract: Testicular cancer (TC) is the most common cancer among young males. Morbidity and Mortality from TC is high in low income

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…[1] In addition to Akar and Bebiş [52] who reported that the majority of study participants were unaware of TSE and did not do it before the health educational intervention. In the same line Etita et al [27] revealed that low practices of TSE among male undergraduate students of the University of Calabar even those that practiced did so irregularly and not as recommended. In addition to Wynd [11] who reported in his study that about 32% had knowledge about TSE, 22% practiced TSE, from male undergraduate and postgraduate students in a British university, but only one respondent reported regular TSE performance.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…[1] In addition to Akar and Bebiş [52] who reported that the majority of study participants were unaware of TSE and did not do it before the health educational intervention. In the same line Etita et al [27] revealed that low practices of TSE among male undergraduate students of the University of Calabar even those that practiced did so irregularly and not as recommended. In addition to Wynd [11] who reported in his study that about 32% had knowledge about TSE, 22% practiced TSE, from male undergraduate and postgraduate students in a British university, but only one respondent reported regular TSE performance.…”
Section: Discussionmentioning
confidence: 85%
“…Early detection of the disease through implementation of health educational guidelines leads to increase cure rate for about 96%, it can be facilitated if men are knowledgeable and encouraged to perform of TSE. [27] This study aimed to evaluate the effect of educational guidelines based on health belief model regarding testicular cancer knowledge, practice and beliefs among male nursing students.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations